Effect of Health Education on the Knowledge and Attitude Regarding the Human Papillomavirus Vaccine among Adolescent School Girls of a City in Western Maharashtra - Apurva U, Tekawade; Muralidhar P, Tambe; Malangori A, Parande; Poonam V, Sancheti; Pradip S, Borle (Indian Journal of Community Health, 2024)
Background: Human papillomavirus vaccine is effective in preventing cervical cancer and is especially recommended for girls above nine years of age. Understanding the level of awareness and attitude of the target population towards the HPV vaccine is imperative to create awareness where necessary. Aim and Objectives: To assess the baseline knowledge, attitudes, and behaviours concerning HPV vaccine among adolescent school girls in urban area, and to investigate the impact of health education on these parameters. Study design: Quasi-experimental Study setting: Secondary school in Pune city Target population: Adolescent girls Methods and Material: Calculated sample size was 200. A school was chosen randomly. All the willing female students from 8th-10th standards were enrolled. Awareness about HPV infection and vaccination, attitude and practices were assessed at the baseline and two weeks after the health education intervention, using a self-administered structured questionnaire. Results: Initially, only 2.5% had heard about the HPV vaccine and none had received it. Following health education, the proportion of students who correctly answered the questions regarding the HPV vaccine, diseases prevented and who can take the vaccine increased significantly by 94%, 71.5% and 72% respectively. Positive attitude regarding the risk of HPV infection and age for vaccination improved significantly by 78.5% and 48% respectively. Vaccine seeking behaviour improved significantly by 17.5%. Conclusions: Adolescent school girls had poor baseline knowledge and attitude regarding the HPV vaccine and health education significantly improved the same.